Knowledge, Attitudes, and Practices (KAP) on Tuberculosis (TB) Among Mining Communities in Gombe State, Nigeria - Abdulkarim, Suraj; John , Stephen; Abdulkarim Kwami, Ibrahim; Balogun, Paul; Abdullahi, Ali Adamu; Garba, Muhammed (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Tuberculosis (TB) remains a significant public health challenge, particularly in underserved mining communities where occupational hazards, poor living conditions, and limited healthcare access exacerbate the disease burden. This study assessed the knowledge, attitudes, and practices (KAP) related to TB among mining communities in Gombe State, Nigeria, using a cross-sectional design with 292 participants. Statistical analyses, including frequency table, multivariate logistic regression, Chi-square Automatic Interaction Detection (CHAID), and latent class analysis, were employed to identify key predictors and subgroups. The findings revealed significant gaps in TB knowledge, with education level being the strongest predictor of accurate transmission knowledge (aOR = 5.60 for higher education, p < 0.001). Stigmatizing attitudes were prevalent, particularly among males with no formal education (41.2%) and those who believed TB is incurable (52.6%). Three distinct practice subgroups were identified: proactive practitioners (24%), moderate practitioners (42%), and low practitioners (34%). The study underscores the need for targeted interventions to address knowledge gaps, reduce stigma, and improve prevention practices. Recommendations include community education campaigns, stigma reduction programs, and tailored interventions for low-practice subgroups. These findings contribute to the global effort to combat TB by providing evidence-based insights for improving TB management in mining communities.